Sensibilidade antimicrobiana in vitro de isolados brasileiros de Lawsonia intracellularis - Ricardo Pereira Laub (2018)
Porcine Proliferative Enteritis, caused by the bacterium Lawsonia intracellularis, is an enteric disease with worldwide distribution. Several studies showed high prevalence of the disease worldwide. The clinical signs observed are diarrhea, weight loss, emaciation accompanied by reduction in feed conversion and in daily weight gain. The most effective form of treatment is antimicrobial therapy. Therefore, the objective of this study was to determine the minimum inhibitory concentration in vitro of ciprofloxacin, lincomycin and tiamulin against L. intracellularis Brazilian isolates. As L. intracellularis is an obligate intracellular microorganism, a minimum inhibitory concentration evaluation was performed for extracellular and intracellular activities of the antimicrobials. The extracellular and intracellular activities for ciprofloxacin and tiamulin showed the best results. It was shown that the lower concentrations of the active principles were able to inhibit the growth of the bacterium for both isolates, although the ciprofloxacin presented moderate concentration in the two duplicates tested for the isolate BRPHE02-E8 (varying of 8 and 4 ìg / mL). The same did not occur with lincomycin, which had high concentrations ( 128 ìg / mL) in all the tests performed and for all tested isolates. Therefore, the two brazilian isolates of L. intracellularis tested in this study had greater sensitivity to ciprofloxacin and tiamulin when compared to lincomycin.